Drawing boundaries : architectural images in Qing China - Chung, Anita (University of Hawaii Press, 2004)
"Qing China (1644-1912) witnessed a resurgence in architectural painting, a traditional subject category known as jiehua, or boundary painting. Drawing Boundaries concerns itself with the symbolic implications of this impressive and little studied reflorescence